Fishery and biology of Priacanthus hamrur (Forsskal) along the Indian coast - Sivakami, S; Raje, S G; Khan, M Feroz; Shobha, J K; Vivekanandan, E; Rajkumar, U (Indian Journal of Fisheries, 2011)
Fishery trend of bull's eye (Family:Priacanthidae) along the Indian coast andsome biological aspects of Priacanthus hamrur (Forsskal) off Cochin are presentedin this paper. Coastwise, the resource is landed more in the west coastfrom a depth range of 20-150m than the east coast, from a depth range of 10-80m. Seasonally, priacanthids were abundant during October-March along thenorth west coast and during December - March and August-October along thesouth west coast. P. hamrur prefers pelagic crustaceans followed by fishes andsmaller molluscs as food.lt appears to breed mainly during April-July, sheddingtwo batches of ova. Gonado -somatic indices showed peak values during June inboth sexes. Size at maturity of males and females were 181- 190mm and 191-200mm respectively. Chi -square test indicated females to dominate the population.Fecundity ranged between 1,55,800 and 7,22,313. The V value in the length-weight relationship of the two sexes was statistically significant at 5% level.